IN VITRO EVALUATION OF ANTIDIABETIC AND CYTOTOXICITY POTENTIALS OF THE RHIZOME EXTRACT OF DRYNARIA QUERCIFOLIA (L.) J. SMITH - PRASANNA G; DEVI R; ISHWARYA G (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: In the present study, an attempt has been made to evaluate the in vitro antidiabetic and cytotoxic potentials of the rhizome extract of Drynaria quercifolia (L.) J. Smith. Methods: In vitro antidiabetic activity was determined by two different assays such as alpha-amylase inhibition assay and glucose uptake assay. The plant extract with three different concentrations was used for this assay. L6 rat myogenic cells were selected and subjected to glucose uptake assay. The cytotoxic activity of the different concentrations of the plant extract on HepG2 cell line was also investigated in vitro through 3-(4,5, dimethythiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay. Results: The findings of the study provide evidence that the rhizome extract of D. quercifolia possesses significant anti-diabetic activity. In MTT assay, the significant cytotoxic effect of plant extract was observed by measuring the percentage of cell viability on the HepG2 cell line. Conclusion: The findings indicated that rhizome extracts of D. quercifolia have potential as a medicinal drug against diabetes mellitus (DM) and liver cancer. Further, studies with in vivo and clinical trials need to be conducted to establish rhizome extract as a safe agent for DM and liver cancer therapy.